Management and cooperat ion of the small and medium textile business (2019)
This book is the result of the multicampus research “Management and cooperation of small and medium textile companies in the regional cluster Bogotá and Antioquia: Case study”, led by the Arte Solidario research group, from the city of Bogotá, and the Research Group in Organization Management (GDO), of the city of Medellín. The main objective of the project was “to establish the contribution made by the management and cooperation of small and medium-sized textile companies; from the articulating axis of shared value, in the achievement of development and social benefit. In the regional cluster: Bogotá and Antioquia (2015-2017)”.